Technology and the Colombian Fique Industry: Drawing from Latin American Expertise, 1880-1938 (2018)
This article examines the technological origins and changes of the Colombian fique (henequen) industry throughout the late nineteenth and early twentieth centuries. It argues that the industry was established and reached significant levels of growth, in part due to the input of Colombian intellectuals, entrepreneurs, and scientists who examined global developments, disseminated useful knowledge, and sought to adapt suitable crops, practices, and technologies to Colombia’s particular needs, settings, and social traits. These individuals looked mainly at Mexico. This history challenges the traditional assumption that Latin American countries generally developed a technological dependence on the North Atlantic nations. Mid-nineteenth-century Mexican inventions turned out to be particularly useful to Colombians seeking to foster small productive units in rural areas. The Colombian fique industry developed initially as “patrimonio de los pobres” (“heritage of the poor”). Attempts to introduce sophisticated, expensive technologies proved futile.